KOMUNIKASI INTERPERSONAL ANTARA GURU DAN MURID TUNARUNGU DAN TUNAWICARA DI SEKOLAH LUAR BIASA AL ISHLAH JATISRONO - Putra, Bintang Permata; Sihabuddin, Sihabuddin (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2025)
ABSTRACT Communication is one of the most basic human activities in everyday life, which allows people to build relationships with each other. Humans are social creatures who depend on each other for survival. For people with disabilities, such as the deaf and speech impaired, or for those without, communication is very important. In essence, communication is a necessity for every individual. However, those who have disabilities rely on senses that still function well, even though they experience difficulties in communicating. In this research, the focus is on discussing interpersonal communication between teachers and deaf and speech-impaired students in interactions at the Al Ishlah Jatisrono special school. Using a qualitative descriptive method approach. And data is collected through observation, interviews and documentation. This research uses an instructional concept based on teachers' communication patterns with students. The results of this research indicate that interpersonal communication is assessed based on the effectiveness of interpersonal communication that occurs between teachers and deaf and speech impaired students. Keywords: Interpersonal Communication, Teachers, Deaf and Speech Impaired Students